Comparison of effects of different methods for deodorizing sturgeon fish (Acipenser sinensis) - Su, Yi (My University, 2019)
In recent years, sturgeon fish (Acipenser sinensis) has become a popular freshwater-farmed fish in China with high nutritional and economic value. However, the utility of the fish flesh is quite low – the unwanted fishy odor caused by lipid oxidation has become a technical problem which needs to be solved. In this study, the raw material and nutritional characteristics of different parts of sturgeon were systematically investigated to provide theoretical support for the processing of sturgeon. The fishy odor of the raw material was deodorized by salt solution, acid/alkaline and yeast (Saccharomyces cerevisae) fermentation methods. Sensory evaluation, thiobarbituric acid value (TBARS) and protein loss rate were used as indicators to compare the deodorization effect. A GC-MS method was optimized for the analysis of volatile compounds. The results showed that sturgeon is abundant with basic nutrients, especially fat and protein. A large amount of unsaturated fatty acids were also measured in this study, especially for DHA and EPA. Comparing with other two parts, the fish abdomen has longer and dense fiber. Out of three deodorization method, yeast fermentation was the most effective method for deodorization with reduced protein loss rate and low TBARS value. The type and relative content of volatile compounds detected with GC-MS were significantly lower than before deodorization. The best deodorization effect was achieved with yeast amount of 0.1%, the time of deodorization of 40 min, and the deodorization temperature of 30 °C.
Keywords: deodorization, GC-MS, raw material, sturgeon, volatile compounds